2018
DOI: 10.1101/384842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Personal clinical history predicts antibiotic resistance in urinary tract infections

Abstract: The prevalence of antibiotic resistance in urinary tract infections (UTIs) often renders the prescribed antimicrobial treatment ineffective, highlighting the need for personalized prediction of resistance at time of care. Here, crossing a 10-year longitudinal dataset of over 700,000 community-acquired UTIs with over 6,000,000 personally-linked records of antibiotic purchases, we show that the resistance profile of infections can be predicted based on patient-specific demographics and clinical history. Age, gen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Thus, a faster time-to-readout can be achieved or even a higher noise level can be allowed in an assay, solely by including a specialized computer algorithm into the assay. Even more futuristic may be the ability to predict resistance of pathogens simply by patient history . As of now, machine learning for assisting AST platforms is only bottlenecked by the programming knowledge of those designing platforms, as well as the limited clinical data sets collected in some cases.…”
mentioning
confidence: 99%
“…Thus, a faster time-to-readout can be achieved or even a higher noise level can be allowed in an assay, solely by including a specialized computer algorithm into the assay. Even more futuristic may be the ability to predict resistance of pathogens simply by patient history . As of now, machine learning for assisting AST platforms is only bottlenecked by the programming knowledge of those designing platforms, as well as the limited clinical data sets collected in some cases.…”
mentioning
confidence: 99%
“…In the space of bacterial infection, retrospective analyses of etiology and descriptive studies have been reported in regular intervals 3133 . However, collective and methodical applications of predictive modeling is yet to be extensively implemented in the field of empiric treatment via antimicrobial sensitivity analysis barring a few interesting attempts 34,35 . Also the data used in the existing studies were not publicly available.…”
Section: Discussionmentioning
confidence: 99%